2012
DOI: 10.1007/s00405-012-2136-y
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of nuclear factor-kappa B p50 and p65 and their significance in the up-regulation of intercellular cell adhesion molecule-1 mRNA in the nasal mucosa of allergic rhinitis patients

Abstract: The purpose of the study was to investigate expressions of nuclear factor-kappa B (NF-κB) and intercellular cell adhesion molecule-1 mRNA (ICAM-1 mRNA) in the nasal mucosa of allergic rhinitis (AR) patients. Expressions of NF-κB and ICAM-1 mRNA were studied using immunohistochemistry and reverse transcription-PCR (RT-PCR) in AR tissues and corresponding normal nasal mucosa. The correlation between NF-κB and ICAM-1 mRNA was studied using linear correlation analysis. The results of immunohistochemistry showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Although a previous study reported that the expression levels of ICAM-1 did not increase in the positive control group or decrease in the TNF-α treatment group,26 ICAM-1 has been reported to play an important role in local inflammation and eosinophil infiltration, and gene expression is regulated by NF-κB 27. Wang et al7 showed that the expression of NF-κB p50 and p65 has a significant positive correlation with that of ICAM-1 mRNA, and NF-κB plays an important role in ICAM-1 transcription in the nasal mucosa of AR patients. The decrease in the expression of ICAM-1 protein suggests that local inhibition of NF-κB leads to a decrease in the transcription of ICAM-1 and prevents adhesion of eosinophils on endothelial cells, thus inhibiting eosinophil infiltration in the nasal mucosa.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although a previous study reported that the expression levels of ICAM-1 did not increase in the positive control group or decrease in the TNF-α treatment group,26 ICAM-1 has been reported to play an important role in local inflammation and eosinophil infiltration, and gene expression is regulated by NF-κB 27. Wang et al7 showed that the expression of NF-κB p50 and p65 has a significant positive correlation with that of ICAM-1 mRNA, and NF-κB plays an important role in ICAM-1 transcription in the nasal mucosa of AR patients. The decrease in the expression of ICAM-1 protein suggests that local inhibition of NF-κB leads to a decrease in the transcription of ICAM-1 and prevents adhesion of eosinophils on endothelial cells, thus inhibiting eosinophil infiltration in the nasal mucosa.…”
Section: Discussionmentioning
confidence: 95%
“…However, information regarding the association of local NF-κB inhibition with allergic inflammation in AR is limited, although it has been demonstrated in humans and animal models that NF-κB is up-regulated in the nasal mucosa of patients with allergic rhinitis (AR) 789…”
Section: Introductionmentioning
confidence: 99%
“…As an important regulator of proinflammatory gene expression, synthesis of cytokines such as IL-1 β , IL-6, IL-8, and TNF- α is mediated by NF- κ B. Activation of NF- κ B may induce human inflammatory diseases [150, 151]. It was reported that negatively charged poly(acrylic acid-) conjugated GNP activated the NF- κ B signalling pathway in THP-1 cells.…”
Section: The Mechanisms Of Immunomodulation Induced By Npsmentioning
confidence: 99%
“…We employed serial nasosorption sampling and measured levels of soluble chemokines and cytokines using a multiplex immunoassay system. In addition, nasal epithelial curettage samples were taken for analysis of mRNA (transcriptomics) for intercellular cell adhesion molecule-1 (ICAM-1) that is elevated in the nasal mucosa in allergic rhinitis [ 33 ].…”
Section: Introductionmentioning
confidence: 99%